Significant coercivity enhancement at low temperatures in magnetically oriented cobalt ferrite nanoparticles - Tancredi, Pablo (2019)
The present work describes a synthesis and characterization strategy employed to study the magnetic anisotropic properties of a diluted nanoparticulate system. The system under analysis is composed of monodisperse and highly crystalline 16 nm Co0.5Fe2.5O4 nanoparticles (NPs), homogenously dispersed in 1-octadecene. Owing to the liquid nature of the matrix at room temperature, the relative orientation of the nanoparticle easy axis can be controlled by an external magnetic field, enabling us to measure how the magnetic properties are modified by the alignment of the particles within the sample. In turn, by employing this strategy, we have found a significant hardness and squareness enhancement of the hysteresis loop in the magnetically oriented system, with the coercive field reaching a value as high as 30.2 kOe at low temperatures. In addition, the magnetic behavior associated with the system under study was supported by additional magnetic measurements, which were ascribed to different events expected to take place throughout the sample characterization, such as the melting process of the 1-octadecene matrix or the NP relaxation under the Brownian mechanism at high temperatures.